Therapeutic Effect of Curcumin Oral Gel on Salivary Epidermal Growth Factor and Lactate Dehydrogenase Levels in Relation to Oral Mucositis in Head and Neck Cancer Patients Undergoing Concurrent Chemoradiation - Rouaa S. Farhan; Fawaz D. Al-Aswad (Diyala Journal of Medicine)
Background: Curcumin is a traditional herbal medication, which has shown promise in a variety of pharmacologic applications. Epidermal growth factor an amino acid polypeptide found in saliva and other bodily fluids, which promotes cell proliferation and renewal. Lactate dehydrogenase is classified as altered protein markers present in saliva, and its levels showed significantly elevated in head and neck cancer. To study the effect of curcumin oral gel on levels of salivary epidermal growth factor and lactate dehydrogenase in head and neck cancer patients receiving concurrent chemoradiation induced oral mucositis.